Työtaitojen kehittyminen erityisammattikouluvaiheen aikana - Matikainen, Tuula (1994)
The research objective was to develop methods and practices for special vocational schools for the mentally handicapped. The study was carried out in the special vocational schools of Perttula and Alavus as a time series during the years 1984 - 1990 (n = 224). The data was collected in cooperation with teachers, counsellors, personnel working within student welfare and office staff. Students from eight different two-year courses (weaving, domestic science, car cleaning and garage work, cleaning work, woodwork, caretaking and maintenance of buildings and grounds, warehouse and stock-taking work and embroidery) participated in the study. Of the students 64 % had multiple handicaps. Modified comprehensive school had been completed by 63 % and training school by 9 % of the students. Other special classes had been attended by 4 % of the students and 5 % were older students who had completed elementary school. Before entering the special vocational school most of the students had done an additional year in a special college. The research variables comprised 1) the Perttula Working Skill Rating Scale, 2) a skill acquisition rating scale designed on the basis of the vocational training curriculum, 3) intelligence tests (Raven and WISC or WAIS) and 4) the Wartegg test. In the intelligence tests (WAIS or WISC) the mean value of the total score was 66. The minimum was 40 and the maximum 99. Neurological and psychological disorders, opposition to authority were found in several of the Wartegg test results. The first follow-up measurement of the first-year course was carried out in December 1984 and the second in May 1985. Thereafter, measurements were carried out every December and May till 1990. Complete data for 91 students was obtained for all four measurements of the Perttula Working Skill Rating Scale. Factors were named after the loading points and other relevant structures as follows: working skills, perception of instructions, sociability and adjustment. The main method of analysis was multivariate analysis. T-tests and variance analysis were applied to determine the differences between the groups. Working skills measured by the Perttula Working Skill Rating Scale developed very significantly during the two special vocational school years. Of the new mean value variables adjustment was evaluated the best and sociability the second best. Working skills were assessed to be better mastered than the perception of instructions. The connection between level of intelligence and perception of instructions was almost significant. There was an almost significant difference in working skills and a very significant difference in the perception of instructions between the Raven groups. The results of the four measurements concerning the achievement of curriculum objectives are reported for 50 students in the following courses: woodwork, domestic science, weaving and embroidery. Very significant differences between the different courses were detected in the evaluations of the achievement of curriculum objectives. The curriculum objectives were best achieved in weaving, the second in domestic science, the third in woodwork and the fourth best in embroidery.